Pension Entitlements and Net Wealth in Austria - Markus Knell; Reinhard Koman (Oesterreichische Nationalbank (OeNB), 2022)
This study combines data from the HFCS (Household Finance and Consumption Survey) and the social security registry to estimate the present value of public pension entitlements for Austria in the year 2017. The household averages of the present value of pension entitlements and of private net wealth turn out to be similar (both amounting to around e250,000) which is in line with the results for other countries like Switzerland, Germany and the US. Since pension entitlements are more equally distributed than other assets most inequality measures for augmented wealth (the sum of pension entitlements and net wealth) are lower than for net wealth. The Gini coefficient for Austria, e.g., decreases from 0.73 (for net wealth) to 0.53 (for augmented wealth) which is again fairly similar to the results for other countries. Furthermore, it is shown that the main results are robust to many alternative specifications. In particular, estimates based on statistical matching and on direct survey information lead to surprisingly similar results. The same is true for specifications with homogeneous or heterogeneous life expectancy and with retirement at the statutory or the individually expected retirement age. Finally, the paper compares the results to the ones of the related literature, sums up the limitations of the approach and discusses why the results have to be interpreted cautiously due to the fact that pension entitlements and net wealth are not perfectly commensurable concepts.
Keywords: D31; H55; J32; 330; Net wealth; Net worth; Pension entitlements; Augmented wealth; Life cycle; HFCS